The Preprocessing and Probing Technique of Open Capacitated Vehicle Routing Problem with Split and Time Deadline (OCVRP-St) Model In Rubbish Transportation Problem - Irmeilyana Irmeilyana; Fitri Maya Puspita; Indrawati Indrawati; Fitra Nur Azizah (International Journal of Advances in Applied Sciences, 2013)
The activity of rubbish transportation in Palembang is one of the applications of Vehicle Routing Problem (VRP) in transporting rubbish in Sako Palembang by applying preprocessing and probing techniques to obtain simplest OCVRP model. The solution is conducted by using LINDO software. The results show that the optimal routes in Sukarami before and after applying the tehniques are the same routes. In addition, we obtain the reduction of constraints and variables, the reduction of iteration numbers and the optimal value did not change.